The reality of God and historical method: apocalyptic theology in conversation with N.T. Wright - Adams, Samuel V. (New explorations in theology, 2015)
"After a flurry of heated debates in the mid-twentieth century over the relationship between faith and history, the dust seems to have settled. The parties have long since dispersed into their separate camps. The positions are entrenched and loyalties are staked out. This first volume in the New Explorations in Theology is a deliberate attempt to kick up the dust again, but this time as a constructive development of what is now being called 'apocalyptic theology.' Samuel Adams argues that any historiography interested in contributing to theological knowledge must take into consideration, at a methodological level, the reality of God that has invaded history in Jesus Christ. He explores this idea in critical dialogue with the writings of New Testament historian and theologian N.T. Wright, whose work has significantly shaped the current conversation on this problem. The Reality of God and Historical Method is a fresh, bold and interdisciplinary exploration of the question: How is it possible to say that a particular historical person is the reconciliation of the world?"--Provided by publisher